Inkjet-printed optoelectronics. Issue 3 (23rd December 2016) - Zhan, Zhaoyao; An, Jianing; Wei, Yuefan; Tran, Van Thai; Du, Hejun
Abstract : A systematical overview of optoelectronics fabricated by inkjet printing techniques. Abstract : Inkjet printing is a powerful and cost-effective technique for deposition of liquid inks with high accuracy, which is not only of great significance for graphic applications but also has enormous potential for the direct printing of optoelectronic devices. This review highlights a comprehensive overview of the progress that has been made in optoelectronics fabrication by the inkjet printing technique. The first part briefly covers the droplet-generation process in the nozzles of printheads and the physical properties affecting droplet formation and the profiles of the printed patterns. The second section outlines the recent activities related to applications of inkjet printing in optoelectronics fabrication including solar cells, light-emitting diodes, photodetectors and transparent electrodes. In each application field, the challenges with the inkjet printing process and the possible solutions are discussed before a few remarks. In the last section, a brief summary on the progress of inkjet printing fabrication of optoelectronics and an outlook for future research effort are presented.